Halide perovskites scintillators: unique promise and current limitations. Issue 35 (10th June 2021) - Moseley, Oliver D. I.; Doherty, Tiarnan A. S.; Parmee, Richard; Anaya, Miguel; Stranks, Samuel D.
Abstract : The origins of the remarkable performance of halide perovskite scintillators are presented, along with solutions to the challenges facing the field, followed by a discussion of applications that will benefit from the unique properties of these materials. Abstract : The widespread use of X- and gamma-rays in a range of sectors including healthcare, security and industrial screening is underpinned by the efficient detection of the ionising radiation. Such detector applications are dominated by indirect detectors in which a scintillating material is combined with a photodetector. Halide perovskites have recently emerged as an interesting class of semiconductors, showing enormous promise in optoelectronic applications including solar cells, light-emitting diodes and photodetectors. Here, we discuss how the same superior semiconducting properties that have catalysed their rapid development in these optoelectronic devices, including high photon attenuation and fast and efficient emission properties, also make them promising scintillator materials. By outlining the key mechanisms of their operation as scintillators, we show why reports of remarkable performance have already emerged, and describe how further learning from other optoelectronic devices will propel forward their applications as scintillators. Finally, we outline where these materials can make the greatest impact in detector applications by maximally exploiting their unique properties, leading to dramatic improvements in existing detection systems or introducing entirely new functionality.